PENGARUH DUKUNGAN ORANG TUA DAN OPTIMISME MASA DEPAN TERHADAP MOTIVASI BEPRESTASI SISWA EKONOMI - Frisca Fawzyah; Yulhendri Yulhendri; Rani Sofya (Universitas Negeri Padang, 2019)
The study aims to find out and analyze: Parental support, optimism for the future toward achievement motivation Student at SMAN 2 Solok. The type of this research was a correlational. The technique of sampling in this study was the simple random sampling, with a sample of 162 students. Data collected through in terviews, questionnaires, and documentation as a reference in research. Method analysis was the Path analysis. classified in to quantitative study using survey research methods. To test the hypothesis by using test. The results showed that: 1) Parental support significantly influence the achievement motivation. 2) optimisme future significantly influence the achievement motivation. 3) the Parental support significant effect the optimisme future.Keyword: Parental support, Peer social support, optimisme future, achievement motivation